Green Halal Business Model: Integrating Maqasid al-Shari'ah into Circular Economy Practices for Sustainable Competitive Advantage - Ade Khadijatul Z. Harahap; Rahmat (Yayasan Darussalam Bengkulu, 2026)
Background: This study aims to propose an integrative framework of the